Lec_9_The_multiplier

Lec_9_The_multiplier - EC 400 Total Expenditure E = A0 –...

This preview shows pages 1–7. Sign up to view the full content.

EC 400 1 Total Expenditure E = A 0 –c r + b·(1- τ ) ·Y E Y E E=Y Total Expenditure E = A 0 r + b·(1- ) ·Y Y Total Expenditure E = A 0 r + b·(1- ) ·Y E E = Y Y A 0 -c r

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
EC 400 2 Total Expenditure E = A 0 –c r + b·(1- τ ) ·Y E E=Y E = A 0 -c r + b(1- τ )Y Y Slope = b(1- τ ) A 0 -c r Total Expenditure E = A 0 r + b·(1- ) ·Y E E=Y E = A 0 -c r + b(1- τ )Y Y Slope = b(1- τ ) A 0 -c r Y* Total Expenditure E = A 0 r + b·(1- ) ·Y E E=Y E = A 0 -c r+b(1- τ )Y E = A 1 -c r + b(1- τ )Y Y Slope = b(1- τ ) A 0 -c r E 0 c r + b(1 Y 0 * A 1 -c r Y 1 *
EC 400 3 Total Expenditure E = A 0 –c r + b·(1- τ ) ·Y E E=Y E = A 0 -c r+b(1- τ )Y E = A 1 -c r + b(1- τ )Y Y Slope = b(1- τ ) A 0 -c r E 0 c r + b(1 Y 0 * A 1 -c r Y 1 * Total Expenditure E = A 0 r + b·(1- ) ·Y E E=Y E = A 1 -c r + b(1- τ )Y Y Slope = b(1- τ ) A 0 -c r E = A 0 -c r + b(1- τ )Y Y 0 * A 1 -c r Y 1 * E E=Y E = A 1 -c r + b(1- τ )Y The Multiplier The change in spending = A 1 –A 0 = Δ A The change in output = Δ A /{1-b(1- τ )} > Δ A Y Slope = b(1- τ ) A 0 -c r E = A 0 -c r + b(1- τ )Y Y 0 * A 1 -c r Y 1 *

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
EC 400 4 The Multiplier • We have two equations and two unknowns. • The unknowns are E and Y The Multiplier • We have two equations and two unknowns. • The unknowns are E and Y • Equations are E = Y E = A 0 –c r + b·(1- τ ) ·Y The Multiplier E = Y E = A 0 r + b·(1- ) ·Y
EC 400 5 The Multiplier E = Y E = A 0 –c r + b·(1- τ ) ·Y Y = A – c r+b·(1 ) ·Y Y A 0 c r + b(1- ) Y The Multiplier E = Y E = A 0 r + b·(1- ) ·Y Y = A – c ) ·Y Y A 0 ) Y Y - b·(1- )·Y = A 0 r + b·(1- ) ·Y- b·(1- )·Y The Multiplier E = Y E = A 0 r + b·(1- ) ·Y Y = A 0 – c ) ·Y Y A ) Y Y - b·(1- )·Y = A 0 r + b·(1- ) ·Y- b·(1- )·Y [1- b·(1- )]·Y = A 0 r

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
EC 400 6 The Multiplier E = Y E = A 0 –c r + b·(1- τ ) ·Y Y = A – c r+b·(1 ) ·Y Y A 0 c r + b(1- ) Y Y - b·(1- )·Y = A 0 r + b·(1- ) ·Y- b·(1- )·Y [1- b·(1- )]·Y = A 0 r Y* = {A 0 r} / [1- b·(1- )] The Multiplier E = Y E = A 0 r + b·(1- ) ·Y Y = A 0 r + b·(1- ) ·Y Y - b·(1- )·Y = A 0 r + b·(1- ) ·Y- b·(1- )·Y [1- b·(1- )]·Y = A 0 r Y* = {A 0 r} / [1- b·(1- )] Y* = intercept/{1 – slope} E E=Y E= A 1 -c r+b(1- τ )Y The Multiplier Y 0 *= {A 0 -c r}/ {1-b(1- τ )} Y Slope = b(1- τ ) A 0 -c r E = A 0 -c r + b(1- τ )Y Y 0 * A 1 -c r E =
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 09/14/2009 for the course EC 400 taught by Professor Cover during the Spring '09 term at Alabama.

Page1 / 18

Lec_9_The_multiplier - EC 400 Total Expenditure E = A0 –...

This preview shows document pages 1 - 7. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online